Choroba i śmierć za murami klasztoru panien norbertanek w I mbramowicach w świetle Kroniki Zofii Grothówny z lat 1703-1741 - Mierzejewska, Milena (Saeculum Christianum. Pismo Historyczne, 2016)
The article describes illness and death behind the walls of the convent of the Norbertine in Ibramowice in light of The Chronicle Sophia Grothówna from the years 1703-1741. Health problems and death in human life are two inevitable events. As a people we know this is unavoidable and we will meet every existence. Sisters of Mary also were afflicted with minor or major health problems. The nuns lived in damp conditions. At the monastery Imbramowice flows flows the river Dłubnia, causing a humid environment. Nuns in Imbramowice had to contend with difficult housing conditions after a fire in 1710. Norbertine’s coped with the diseases in various ways:leaving for treatment to spas (with the consent of the bishop and the abbess), or waiting for assistance of a barber, doctors came less frequently. The article contains also diseases to which the sisters suffered. In the second part, the paper describes the death of sisters and everything that is associated with it. Every act of dying featured in the pages of The Chronicle abbes Grothówna was dramatic. After the death of a Norbertine followed by a funeral, if the nun exercised a high function at the monastery burial was very solemn and distinguished guests arrived. The Sisters of Mary also organized refreshments for the poor people, to help the dead and prayed for a specified period of time. The article includes a list of all the sisters residing at the monastery in Imbramowice over the years 1703-1741. The table presents information: date of commencement of the novitiate, professed, perpetual function each nun and date of death.